2018
DOI: 10.3341/kjo.2017.0118
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Demographic Characteristics of Blepharoptosis in Korea: A 24-year Experience including 2,328 Patients

Abstract: PurposeTo describe the demographics, relative incidence of subtypes, and clinical characteristics of blepharoptosis in Korean patients.MethodsThis is a retrospective, observational case series consisting of 2,328 patients who underwent ptosis surgery from 1991 to 2014 at a tertiary referral hospital in Korea. The patients were classified according to the type of ptosis and the evaluation of clinical characteristics including levator muscle function (LF) and degree of ptosis.ResultsOf the 2,328 patients, 1,815 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Similar trends were observed in our study with 60% and 40% male and female distribution. Left sided congenital ptosis is reported more frequently in literature 7,9,12 . In our study, right sided congenital ptosis was more common.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Similar trends were observed in our study with 60% and 40% male and female distribution. Left sided congenital ptosis is reported more frequently in literature 7,9,12 . In our study, right sided congenital ptosis was more common.…”
Section: Discussionmentioning
confidence: 98%
“…Twnty three percent patients in our study had bilateral congenital ptosis. Bilateral congenital ptosis is reported about 3-7% in different reports 4,7,12 . In our study bilateral cases are reported in far major number.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies report different prevalence of congenital and acquired ptosis. Lee et al, in their hospital-based study in Korea, found congenital ptosis in 78% of cases (4). In contrast, in Chicago, Lim et al, also in a hospital-based study, reported that the most common type of ptosis was aponeurotic ptosis (5).…”
Section: Methodsmentioning
confidence: 95%